PERENCANAAN STRATEGI BERSAING SEKOLAH DALAM MENINGKATKAN JUMLAH PESERTA DIDIK BARU DI SALAH SATU SEKOLAH SWASTA SALATIGA 1 - Dewa Made Dwi Kamayuda (Kelola: Jurnal Manajemen Pendidikan, 2016)
This study aimed to develop competitive strategy planning in increasing number of new students in one of private schools in Salatiga. The Design of the study is research & development, but it is limited to the product design stage alone that produce schools competitive strategy planning in increasing the number of new students. Research instruments for gathering data are observation, interviews, FGD and study documents. Data Analysis used SWOT analysis to analyze the internal and external factors such as the school's strengths, weaknesses, opportunities and threats in determining the appropriate competitive strategies for schools. The result of SWOT analysis indicated that the school is in quadrant position SO (Strength Opportunity), which supports an aggressive strategy by using the power of the internal environment of the school to seize the opportunities from external environment. Competitive strategy planning of the school which suggested is differentiation strategy namely: making program "community service" in the form of "students service community", building cooperation and trust with the two primary schools under the same foundation, forming clubs academic achievement and non-academic, maximizing learning extracurricular through the program of "students exhibition" that can also be a program of "open house" of the school, maximizing the potential of teachers through seminars, training or workshops, maximizing the facility orphanage, making a jointly program of "parents & students fun day", socializing to public and private schools, churches and Christian communities regularly.